PROJECT BASED LEARNING : DEVELOPMENT OF EARLY CHILDHOOD ABILITIES - Evi Maulidah; Fajar Abdillah (FORPIM PTKIS ZONA TAPAL KUDA, 2023)
Project-based learning is a recommended educational style because it can encourage students to be critical thinkers, creative problem solvers, adept at solving problems, and knowledgeable about both everyday problems and abstract world issues. The purpose of this essay is to describe the use of project-based learning in the education of young children and the potential benefits of this type of instruction. The technique is library research, which involves gathering information from numerous works of literature and turning it into intelligible information. About the application-based, six-step PAUD implementation of project-based learning. Children's abilities in all areas of their development can be stimulated by the use of this learning technique.